Sensation Seeking and Hedge Funds - BROWN, STEPHEN; LU, YAN; RAY, SUGATA; TEO, MELVYN (Journal of Finance, 2018)
ABSTRACT We show that, motivated by sensation seeking, hedge fund managers who own powerful sports cars take on more investment risk but do not deliver higher returns, resulting in lower Sharpe ratios, information ratios, and alphas. Moreover, sensation‐seeking managers trade more frequently, actively, and unconventionally, and prefer lottery‐like stocks. We show further that some investors are themselves susceptible to sensation seeking and that sensation‐seeking investors fuel the demand for sensation‐seeking managers. While investors perceive sensation seekers to be less competent, they do not fully appreciate the superior investment skills of sensation‐avoiding fund managers.